Ultrasensitive, Specific, and Rapid Detection of Mycoplasma pneumoniae Using the ERA/CRISPR–Cas12a Dual System - Deng, Zhongliang; Hu, Haiyang; Tang, Dan; Liang, Jiaxin; Su, Xiaoling; Jiang, Tingqing; Hu, Xipan; Ying, Wanqin; Zhen, Deshuai; Xiao, Xilin; He, Jun (Frontiers in Microbiology, 2022)
Mycoplasma Pneumoniae can cause severe respiratory tract infections, which are similar to the clinical manifestations caused by other respiratory pathogens and are prone to misdiagnosis. Diagnostic methods of M. pneumoniae include isolation and culture, antibody detection, fluorescence quantitative PCR and so on, but variant shortcomings in time, cost, convenience and sensitivity. CRISPR/Cas system, known as a "gene magic scissor", is a nucleic acid detection system, while its sensitivity cannot reach the clinical detection limit (LOD). Most of them must combine with nucleic acid amplification technology. In this study, we developed a rapid detection of M. pneumoniae with the ERA/CRISPR-Cas12a dual system, which used high specificity and collateral cleavage activity of CRISPR/Cas12a system, combined with Enzymatic Recombination Amplification (ERA) technology with strong amplification ability. And the method allowed the results were observed by the portable fluorometer or visualized by the naked eye with the dipstick, which can be obtained in about 30 min. The LOD of ERA/CRISPR-Cas12a fluorescence detection system and dipstick system of M. pneumoniae were 1 and 100 copies/μL, respectively, and the sensitivity of the fluorescence system was comparable to that of the commercial fluorescence quantitative PCR Kit, while the dipstick system was lower; the specificity of the two interpretation methods was 100%, and there was no cross-reaction with other pathogens. In the evaluation of 92 clinical samples, the positive predictive agreements of the ERA/CRISPR-Cas12a fluorescence system and dipstick system with qPCR detection were 100% and 92.86%, respectively. The negative predictive agreement of the two interpretation methods was 100%. In conclusion, the study established a portable, rapid, low-cost, ultrasensitive and specific method for early and rapid diagnosis of M. pneumoniae nucleic acid to meet the needs of on-site rapid detection in primary health institutions.